Comparative genomics for Agmasoma sp. (Microsporidia) parasitising invasive Carcinus aestuarii and Carcinus maenas in Argentina - Bojko, Jamie (2023)
Carcinus sp. are global aquatic invaders and carriers of several parasites, including a taxonomically unrecognised microsporidian recently observed from Argentina. We provide genome drafts for twoparasite isolates, one from Carcinus maenas and one from Carcinus aestuarii, and use multi-gene phylogenetics and genome comparison methods to outline their similarities. Their SSU genes are 100% similar and other genes have an average similarity of 99.31%. We informally name the parasiteAgmasoma carcini, terming the isolates Ac. var. aestuarii and Ac. var. maenas, following the wealth of genomic data available for each. This study follows on from Frizzera et al. (2021), where this parasite was first histologically identified.